Survival in the city - "Adlam, Frances" (Hawthorn; Mimosa McGraw-Hill, 2007)
Max and his partner Ruby are in the final round of THE BRAIN, the most popular TV show of the year. Thousands of people are watching. How will Max and Ruby find their way through the city? How can they compete against Techno Terry and Nigel Nerk?
Donated by "Book Planet", Dated 18-4-2025.
Keywords: Children's stories